2020
DOI: 10.3390/app10030863
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Capture by Alkaline Carbonation as an Alternative to a Circular Economy

Abstract: In order to combat global warming and climate change in a sustainable way, it is necessary to capture the anthropogenic CO2 emitted by different industrial sources and use it as a raw material to obtain a matrix of products for industrial use, such as metal carbonates. Therefore, this work presents the results of CO2 capture and conversion into carbonates using Sr and Ba alkaline solutions in a semi-continuous batch reactor. The results indicate that the effects of morphological characterization, purity of sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(27 reference statements)
1
3
0
Order By: Relevance
“…For Fe uptake, compared to calcium oxide, iron oxide has more potential to be liberated into the solution because of its high constituent. Thus, the condition favors the carbonation process, which is in good agreement with previous studies that have agreed that the most suitable pH for mineral carbonation is greater than 10 [71]. Figure 7 illustrates the DTG curves of raw and carbonated Fe-rich mine waste at initial pH (pH N) and at pH 8-12, which represent the peaks of weight loss that occurred in the temperature interval between 30-1000 • C. Most of the peaks appear at almost similar temperatures but have different weight loss percentages.…”
Section: Carbonation Process Optimization: Effect Of Different Parame...supporting
confidence: 92%
“…For Fe uptake, compared to calcium oxide, iron oxide has more potential to be liberated into the solution because of its high constituent. Thus, the condition favors the carbonation process, which is in good agreement with previous studies that have agreed that the most suitable pH for mineral carbonation is greater than 10 [71]. Figure 7 illustrates the DTG curves of raw and carbonated Fe-rich mine waste at initial pH (pH N) and at pH 8-12, which represent the peaks of weight loss that occurred in the temperature interval between 30-1000 • C. Most of the peaks appear at almost similar temperatures but have different weight loss percentages.…”
Section: Carbonation Process Optimization: Effect Of Different Parame...supporting
confidence: 92%
“…The total reaction for the precipitation of CaCO 3 from carbide slag is shown in eq , and there are some other side reactions in the process, such as eq . When NaOH is introduced, the effect is shown in eqs and. CaC O 3 + CO 2 + H 2 normalO Ca false( HC O 3 ) 2 Ca false( HC O 3 ) 2 + NaOH CaC O 3 + NaHC O 3 + H 2 normalO Ca false( HC O 3 ) 2 + 2 NaOH CaC O 3 + Na 2 CO 3 + 2 H 2 normalO …”
Section: Resultsmentioning
confidence: 99%
“…The total reaction for the precipitation of CaCO 3 from carbide slag is shown in eq , and there are some other side reactions in the process, such as eq . When NaOH is introduced, the effect is shown in eqs and. …”
Section: Resultsmentioning
confidence: 99%
“…Besides these advantages, the investment in oxygen plant and flue gas recirculation system (CAPEX) and the energy consumption of these systems (OPEX) limits the application of oxy-fuel combustion to the conventional coal power plant. For post-combustion capture systems, Cruz-Navarro et al [3] assessed the CO 2 capture and conversion of low volumetric flow rates into carbonates using Sr and Ba alkaline solutions with a simple system to implement in small industries. The study of the reaction showed that a 20-min reaction time is required to maximize the carbonate production.…”
Section: Contributions To This Special Issuementioning
confidence: 99%